European and US constitutionalism / edited by Georg Nolte. - Nolte, Georg, 1959- (Cambridge University Press, 2005)
European constitutionalism is not merely an intra-European phenomenon but it can also be compared to other major forms of constitutionalism. Over the past decade or so issues have emerged which seem to indicate that European constitutional theory and practice is becoming aware that it has developed certain rules and possesses certain characteristics which distinguish it from US constitutionalism and vice versa. This book explores whether such differences can be found in the five areas of 'freedom of speech', 'human dignity', 'duty to protect', 'adjudication' and 'democracy and international influences'. The authors of this book are constitutional scholars from Europe and the United States as well as from other constitutional states, such as Canada, Israel, Japan, Peru and South Africa.